Development of AR Assemblr Teaching Materials Based on Civic Literacy on Behavior Material According to Pancasila Values ​​in Elementary Schools: Pengembangan Bahan Ajar AR Assemblr Berbasis Literasi Kewargaan Pada Materi Perilaku Sesuai Nilai-Nilai Pancasila Di Sekolah Dasar - Wanda Ariesta Islami; Wiwik Okta Susilawati; M. Anggrayni (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This research is motivated by the low civic literacy, especially in the civic knowledge aspect of fifth-grade students in the Pancasila Education subject at SDN 14 Pulau Punjung, which is caused by the limited use of interactive digital technology-based teaching materials in schools. This research aims to develop a valid, practical, and effective Augmented Reality (AR) Book Assemblr teaching material to improve students' civic knowledge. The methodology used in this research is Research and Development (R&D) with a 4D development model (Define, Design, Develop, Disseminate). Data collection instruments used include validation sheets from material and teaching material experts, teacher and student response questionnaires to measure practicality, and questions to evaluate product effectiveness. The results of the study indicate that the AR Book teaching material developed meets the criteria of very valid, with a content validity score of 86.11%, language validity of 82.40%, graphic validity of 89.59%, teaching module validity of 85.37%, and question validity of 85%. This product is also stated to be very practical to use in learning based on the implementation of the teaching module of 88%, as well as the acquisition of a teacher response score of 100% and a student response of 96%. In addition, the AR Book teaching material has proven effective in improving the civic knowledge of fifth grade students, as shown by the results of the teaching material effectiveness test of 90.87%, which is included in the high category.